2010
DOI: 10.1098/rsif.2009.0534
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and analysis of carbon fibre-reinforced polymer composite laminates with embedded circular vasculature

Abstract: A study of the influence of embedded circular hollow vascules on structural performance of a fibre-reinforced polymer (FRP) composite laminate is presented. Incorporating such vascules will lead to multi-functional composites by bestowing functions such as self-healing and active thermal management. However, the presence of off-axis vascules leads to localized disruption to the fibre architecture, i.e. resin-rich pockets, which are regarded as internal defects and may cause stress concentrations within the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 41 publications
(76 reference statements)
1
60
0
Order By: Relevance
“…Two fabrication routes have been demonstrated, with the vascule preform material either laid between plies [15][16][17] or nested in precut recesses within the plies [18] during the stacking sequence. Regardless of the fabrication route utilised, it has been shown that the vascules should be aligned to both the local fibre direction and loading direction to avoid significant reductions in mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Two fabrication routes have been demonstrated, with the vascule preform material either laid between plies [15][16][17] or nested in precut recesses within the plies [18] during the stacking sequence. Regardless of the fabrication route utilised, it has been shown that the vascules should be aligned to both the local fibre direction and loading direction to avoid significant reductions in mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…The critical load case when embedding within composites is compressive, as a greater reliance is placed on the matrix and embedded item to carry load [11,12,13]. This is supported by the experimental work of Shivakumar and Emmanwori [12], which characterised the effects of embedding optical fibres within unidirectional carbon fibre laminates.…”
Section: Introductionmentioning
confidence: 58%
“…The simulated and experimentally observed load deflection gradients of the flexural specimens (groups D and E, Table 2) are shown in Table 7 interlaminar stresses [6,10,11,13]. The finite element results in this section ( Figures 8a and 8b), identify the interlaminar stress concentrations created by embedding the inductively coupled sensors within the flexural strength specimens, aiding with the interpretation of the results of the flexural strength testing (Table 5).…”
Section: Finite Element Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During lay-up, 1.1 mm diameter Polytetraflouroethylene (PTFE) coated wire was lain along four paths that would form the cooling vessels. During curing, molten resin flows around the PTFE coated wire, and after curing, the wires were pulled out leaving a smooth circular unlined internal void [21]. Fittings were glued to the inlet points of each vessel to connect to an air supply.…”
Section: Methodsmentioning
confidence: 99%